Rekayasa Sistem Informasi Absensi Siswa Sekolah Berbasis Internet - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Nora Dery Sofya; Sonia Sonia (Journal of Information System Research (JOSH), 2022)
The world of education, there is still a lot of data management that is done manually, one of which is the management of attendance data. SMP Negeri 1 Unter Iwes, Sumbawa Regency, processing student attendance is still done conventionally. To assist schools in improving services in terms of attendance processing, an attendance data processing application is needed that can be accessed without space and time limits. Based on these problems, research was conducted to build an internet-based attendance application. The development of the Student Attendance Information System was made using PHP programming, MySQL as a database and Codeigniter framework. The system design uses an object oriented approach using the tools of the Unified Modeling Language (UML) and the waterfall as a software development method. The results of the software are tested in terms of functionality using black box testing. The functional tests are in the form of logins, data management (CRUD Data), attendance processes and reports. With the application that is built, it can support school academic activities, in this case BK and teachers to process student attendance data quickly and automatically.